ANALISA CYCLIC VOLTAMMETRY GUNA RECOVERY TEMBAGA PADA LIMBAH ELEKTRONIK PRINTED CIRCUIT BOARDS (PCB) MENGGUNAKAN RELINE - Sugondo, Ebeng; Wijaya, Andy; Proklamanto, Aan Subekti; Reziana, Fedika Gita; Etnanta, Fatiha Nur (Jurnal Ilmiah Teknik Mesin, 2023)
Cyclic voltammetry analysis for copper recovery on printed circuit boards (PCB) electronic waste using Reline (ChCl: Thiourea) has been successfully carried out. The use of Reline solution (ChCl: Thiourea) is included in the deep eutectic solvent (DES) as an alternative for the use of solvents that are cheap, efficient, and safe for the environment. The solvent is formed from a donor (HBD) and acceptor (HBA) bonds with a ratio of 1 mol: 2 mol to water which will produce a eutectic mixture. The results of XRF (X-ray fluorescence spectrometry) on the printed circuit board (PCB) after comminution obtained the highest element, namely copper at 17.91%, and became the object of research observation. All experiments on the cyclic voltammetry test produced irreversible type voltammograms. The addition of more than 50% water in the deep eutectic solvent (DES) affects the peaks of oxidation and reduction, and in theory, the current efficiency is 99.83% and the optimum test results occur at a temperature of 60 oC for testing the Reline type deep eutectic solvent (DES) solution (ChCl: Thiourea) with a potential of Ep = 4.2975 volts and Ep/2 = 4.2971 volts. SEM-EDX analysis results on a platinum plate (Pt) from deep eutectic solvent (DES) ChCl: Thiourea (Reline) capable of spontaneously depositing copper minerals onto the surface of the platinum plate (Pt). Keywords: Reline, Cyclic Voltammetry, Solvent